Spirulina Culture in Bangladesh XII. Effects of Different Culture Media, Different Culture Vessels and Different Cultural Conditions on Coiled and Straight Filament Characteristics of Spirulina - Noor, Parvin; Akhtar, Nasima; Munshi, John Liton; Begum, Sajeda (Bangladesh Journal of Scientific and Industrial Research, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Effects of different culture media (Bd-2, Bd-3, Bd-4 and IFP), different culture vessels (conical flasks, plastic bowls and earthen pots) and different cultural conditions (stock, pilot plant and shade culture) on coiled and straight filament characteristics of Spirulina were studied. Stock culture maintained under special conditions, retained coiled filament characteristics even after 17 years, while Spirulina filaments in pilot ponds lost their coiled characteristics. Food value of the straight filaments was acceptable and their survival capacity was more than that of coiled filaments. Key words: Spirulina, Media culture, Vessels culture, Cultural condition, Filaments character. Â  DOI = 10.3329/bjsir.v43i3.1152 Bangladesh J. Sci. Ind. Res. 43(3), 369- 376, 2008